Killing stalking. 1 - Koogi (Seven Seas Entertainment, 2022)
"Yoon Bum, a scrawny and quiet man, has a crush on one of the most popular and handsome guys in his college: Sangwoo. After the two cross paths again, Yoon Bum's feelings grow in intensity until they become an obsession--and he breaks into Sangwoo's home. But what he sees inside is not the Sangwoo of his fantasies; his dreams of this alluring man abruptly turn into a nightmare." --